THE EFFECT OF EMPLOYEE COMPETENCY AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. FMI AREA BANK INDONESIA PROVINCE OF BANTEN AND DKI JAKARTA - Kun Novaria, Vidy; Pancasasti, Ranthy; Hidayati, Auliya; Pebriani, Ani (Management Science Research Journal, 2022)
In human resources is the most important asset for the company because of its role as the subject of implementing policies and activities that can be demonstrated by its ability. Employee performance is a problem that needs to be considered by the company, because employee performance will affect the quality of the company in facing competition along with the times. Therefore, having quality human resources (employees) is needed so that company goals can be achieved and can improve employee performance . Employee Competence and Work Environment in previous research can improve Employee Performance. Purpose: The purpose of this study is to analyze the basic framework or model that is expected to improve Employee Performance by involving Employee Competencies, and the Work Environment at PT. FMI area BI Banten and DKI Jakarta Provinces. Originality/value: The novelty in this study is that no previous research has been found that discusses the Effect of Employee Competence (X1), Work Environment (X2) on Employee Performance (Y) at PT. FMI area BI Banten and DKI Jakarta Provinces. Research limitations: The limitation in this study is only to analyze the magnitude of the influence of Employee Competence, Work Environment on Employee Performance at PT. FMI area BI Banten Province and DKI Jakarta Design /methodology / approach: The research method is quantitative using a questionnaire assistance tool with an interval scale of 10 points and sampling techniques are carried out by simple random sampling. The number of samples used was 75 respondents who were processed using the Structural Equation Model-Partial Least Square (SEM-PLS). Findings: The results of this study show that Keryawan Competence has a negative and insignificant effect on Employee Performance, the Work Environment has a positive and significant effect on Employee Performance.